Investigation on the Viability Span of Listeria monocytogenes during the Ripening of Brined Şavak Cheese - Patir, Bahri; Güven, Aba Müslüm (My University, 1999)
The purpose of this study was to determine the viability span of listeria monocytogenes during the ripening of brined şavak white cheese which is produced by and has a significant role in the nutrition of people living in Elazi?, Tunceli, Bingöl and Erzincan, Ewes milk was inoculated with various strains (4b, 1/2c and 1/2a) of listeria monocytogenes at the rate of 1.00×103 -1.35×106 cells/ml and then şavak cheese was produced from the milk. The cheese samples were analysed after 0, 15, 30, 60, 90 and 120 days of ripening for the numbers of listeria monocytogenes with the direct plating method and enrichment methods (at 30°C for 48 hours or 7 days). The numbers of listeria monocytogenes were 3.70×105 - 6.88×105 cfu/g in the curd, which fell to 0.50×10-7.08×10 cfu/g in the cheese after 120 days of ripening and the trends were almost identical. The numbers of listeria monocytogenes determined with the enrichment methods, followed different paths during the ripening. The pH of the cheese until day 60, in all series of the samples. Later in the experiment (days 90 and 120) the values increased. It was conluded that it might be possible to isolate listeria monocytogenes from şavak cheese made from raw ewes milk containing a minimum of 1.00×103 cells/ml; using direct isolation rate in enrichment at 30°C for 48 hours is higher than in enrichment at 30°C for 7 days. In addition, it was evident that listeria monocytogenes survive until the end of the ripening process and pose a danger to public health.
Şavak Salamura Beyaz Peynirin Olgunlaşmasi Sirasinda Listeria monocytogenes in Yaşam Süreleri Üzerine Araştirmalar
Keywords: Inocülation; Listeria monocytogenes; Viability span; White cheese